Seven new species and one new species record of Sabatieria (Nematoda: Comesomatidae) from the continental slope of New Zealand - Leduc, Daniel (Zootaxa, 2013)
Sabatieria is the most abundant nematode genus on the upper continental slope of New Zealand but no Sabatieria species have yet been recorded/described from the region’s deep-sea habitats. The present study describes seven new and one known species of this genus from the continental margin of New Zealand. S. bitumen Botelho et al. 2007 was originally described from the South Atlantic Ocean, and is recorded from the first time in the Pacific Ocean. Sabatieria challengerensis sp. n. is characterised by a combination of short cephalic setae, large fovea amphidialis with 3 turns, short arcuate spicules without distal hook, and short tail with cylindrical proximal portion and blunt, rounded distal portion. Sabatieria parapraedatrix sp. n. is characterised by having a slender body, cuticle with striations resulting from fusion of every second lateral row of dots, fovea amphidialis with 2.0–2.5 turns, spicules with distal hook, and short conico-cylindrical tail. Sabatieria bubulba sp. n. is characterised by the presence of a large muscular pharyngeal bulb, secretory-excretory system with large ventral gland at level of intestine and with cuticularised pore opening. Sabatieria exculta sp. n. is characterised by having a slender body, cuticle with faint annulations resulting from fusion of every second or third lateral row of dots, short cephalic setae, a large ventral gland, and long, narrow gubernacular apophyses. Sabatieria balbutiens sp. n. is characterised by having a dorsally-directed mouth opening and assymetrical mouth cavity and spicules with small distal hook. Sabatieria pumila sp. n. is characterised by the combination of short body length, short cephalic setae, spicules with distal hook and short distal lamella, and 8–9 precloacal supplements. Sabatieria bathycopia sp. n. is characterised by having a stout body, short cephalic setae, curved gubernaculum, and spicules with swollen, lightly cuticularised distal tip.